The Effects of Affinity Mediated Clonal Expansion of Premigrant Thymocytes on the Periphery T-Cell Repertoire - Guanyu Wang (Mathematical Biosciences and Engineering)
The immune system maintains a highly diverse T-cell repertoire,which is shaped by active interactions between developing thymocytesand endogenous peptide/MHC molecules through the principle ofpositive and negative selections. Detours et al. developed aquantitative model addressing key immunologic notions such asselection, alloreactivity, and self-restriction. The model was basedon the assumption that the clone size is uniformly distributed inthe naive T-cell repertoire. However, recent biological findingshave indicated that the naive T-cell repertoire is highly skewed,due to the uneven proliferation of premigrant single-positivethymocytes. In this paper, the model is revised to include these newfindings. The effects of the uneven clonal expansion are investigated in detailand their biological significance is discussed. It is found that theuneven clonal expansion can significantly enhance the self-MHCrestriction, while avoiding decreasing the alloreactivity. The clonal expansiontherefore appears to be an additional selection event, resulting infine tuning of the repertoire. In this way, T-cells reaching theperiphery pool can fulfill maximum competence: both highself-restriction and high alloreactivity.